Herpes zoster as a presentation of diabetes mellitus - Verma, Vivek Kumar; Ram, Vidya Sagar; Singh, Prem Shanker; Kumar, Manoj; Awasthi, Sankalp; Kela, Dheeraj (International Journal of Research in Medical Sciences, 2017)
Background: Herpes zoster (HZ) occurs due to reactivation of latent Varicella zoster virus infection and affects in dermatomal pattern. HZ affects elderly and immunocompromised population. Some earlier studies shows that HZ is common in diabetes patients. Our aim was to find out incidence of diabetes mellitus in patients with HZ. Methods: Study was done on newly diagnosed HZ patients attending out door of UPUMS Saifai. Inclusion criteria include newly diagnosed case of HZ without previous history of diabetes. Patients with known immunocompromised state like HIV infection, corticosteroid therapy, chemotherapy, neoplastic disease etc were excluded. Fasting, post-prandial blood sugar and HbA1C of all patients done. Results: 22.54% patients with HZ had diabetes and 7.75% patients had impaired glucose tolerance at presentation. Undiagnosed diabetes is common in HZ patients. Conclusions: Our study indicates that incidence of undiagnosed diabetes is high among HZ patients and hence routine screening for diabetes should be done in all HZ patients.